Usefulness of IGH/TCR PCR studies in lymphoproliferative disorders with inconclusive clonality by flow cytometry. Issue 1 (13th August 2013) - Ribera, Jordi; Zamora, Lurdes; Juncà, Jordi; Rodríguez, Inés; Marcé, Silvia; Cabezón, Marta; Millá, Fuensanta
<x xml:space="preserve">Abstract</x> In up to 5–15% of studies of lymphoproliferative disorders (LPD), flow cytometry (FCM) or immunomorphologic methods cannot discriminate malignant from reactive processes. The aim of this work was to determine the usefulness of PCR for solving these diagnostic uncertainties. We analyzed IGH and TCRγ genes by PCR in 106 samples with inconclusive FCM results. A clonal result was registered in 36/106 studies, with a LPD being confirmed in 27 (75%) of these cases. Specifically, 9/9 IGH clonal and 16/25 TCRγ clonal results were finally diagnosed with LPD. Additionally, two clonal TCRγ samples with suspicion of undefined LPD were finally diagnosed with T LPD. Although polyclonal results were obtained in 47 of the cases studied (38 IGH and nine TCRγ), hematologic neoplasms were diagnosed in 4/38 IGH polyclonal and in 1/9 TCRγ polyclonal studies. There were also 14 PCR polyclonal results (four IGH, 10 TCRγ), albeit nonconclusive. Of these, 2/4 were eventually diagnosed with B‐cell lymphoma and 3/10 with T‐cell LPD. In eight IGH samples, the results of PCR techniques were noninformative but in 3/8 cases a B lymphoma was finally confirmed. We concluded that PCR is a useful technique to identify LPD when FCM is inconclusive. A PCR clonal B result is indicative of malignancy but IGH polyclonal and nonconclusive results do not exclude lymphoid neoplasms. Interpretation of T‐cell clonality should be based on all the available clinical and analytical data. © 2013 International Clinical Cytometry Society